Evaluation of Complications of Peritoneal Dialysis Catheter in Children: A Retrospective Single Center Study - Mohajerzadeh, Leily; Sharifian, Mostafa; Rouzrokh, Mohsen; Ghoroubi, Javad; Amiri, Mohammad; Ghandchi, Ehsan; Qaderi, Shohra (Iranian Journal of Pediatric Surgery, 2021)
Introduction:Peritoneal dialysis is a long-term method of dialysis for children. Peritoneal dialysis, when performed effectively, saves valuable time for children with advanced kidney transplant, till they reach the appropriate age for the kidney transplant. In children, due to their rapid physical growth and the large catheter size, as well as the thin and weak abdominal wall, especially before the age of 4, the complications of catheterization such as catheter leak and incisional hernia are higher than that of adult population. In this study we aim to evaluatethedysfunction and complications of the cathetersof peritoneal dialysis in children. Materials and Methods:We assessedmedical records of all patients, who underwent peritoneal dialysis since 2006 till 2015 at Mofid hospital, Tehran, Iran. Total number of 41 records were evaluated, of which 11 cases were excluded dueto incomplete data and 30 patients were analyzed eventually.Complications of catheter were recorded. Results:We studied 30 patients, 14 males and 16 females; the mean age of the children was 72.6 months(5 to 12 years old). The leading cause of end stage renal disease(ESRD) were primary glomerulopathies. There were total of 3 catheterreplacements,mostly due to peritonitis and catheter obstruction. The incidence of infectious complications was 40.3%. The incidence of all complications was 1 out of 6.4 patients/month. Conclusion: Regarding the high prevalence of catheter-related complications in children undergoing chronic peritoneal dialysis, especially infectious complications, adopting standard surgical technique of catheter insertion accompanied bywell trained peritoneal dialysis team isessential to prevent the complications and to increase the functional life span of the catheter and to enhance the quality of life of the patient.